EVALUATION OF THE FUNCTIONAL STATE OF THE ORGANISM ON THE BASIS OF THE DANGEROUS SAFETY CRITERIATITLE OF THE ARTICLE - Іванець, Ольга Борисівна; Кулаков, Павло Іванович; Шкіндер, Анна Петрівна; Кулакова, Анна Павлівна (Science-based technologies, 2019)
The paper proposes an approach to the evaluation of the functional state of an organism by evaluating its components. As an integral indicator, it is proposed to use a quantitative indicator of the risk of deviation of the parameters of each subsystem of the organism from the normalized values. To evaluate the functional state of the organism, it is proposed to use a criterion assessment of the risk of deviation from the norm of the constituent subsystems of the organism in order to predict the occurrence of a negative event. It is suggested to use the Jordan function for such estimation based on the results of measurement and measurement control of organism parameters. The function variable is determined on the basis of the results of the experiment and the expert evaluation of the relationship between the results of the measurement of the organism’s parameters and the likelihood of further going beyond tolerance. Determination of the tolerance limit symmetrically relative to the nominal value of the controlled parameter of the organism makes it possible to predict the dependence of the quantitative indicator of the danger of deviation of this parameter from the norm, from the result of its measurement when the controlled parameter is found within the tolerance. The proposed approach makes it possible to formalize the assessment of the functional status of subsystems of the organism as a single component and can be used in analyzing the work of the organism for the purposes of medicine and control of parameters of a biological object for the purpose of complex evaluation. Using this approach allows us to formalize the process of evaluating the body to improve the reliability of decision-making in the tasks of medical direction